2020
DOI: 10.2196/18503
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Global Health Development/Eastern Mediterranean Public Health Network and the Eastern Mediterranean Field Epidemiology Training Programs in Preparedness for COVID-19

Abstract: The World Health Organization (WHO) declared the current COVID-19 a public health emergency of international concern on January 30, 2020. Countries in the Eastern Mediterranean Region (EMR) have a high vulnerability and variable capacity to respond to outbreaks. Many of these countries addressed the need for increasing capacity in the areas of surveillance and rapid response to public health threats. Moreover, countries addressed the need for communication strategies that direct the public to actions for self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 10 publications
0
37
0
2
Order By: Relevance
“…18 Besides the protracted conflicts in many countries in the region, lack of infrastructure, limited resources, inadequate prevention control practices, poor preparedness capacity, and inadequate Awareness and response to Coronavirus disease (COVID-19) epidemic among the Arab Mhammad Saleh laboratory infrastructures and resources in many countries in the EMR are among the main barriers to adequately detect and respond to COVID-19. 17 Nsour et al in this study highlights the contribution of EMR's FETPs to the preparedness capacities in countries in the EMR to respond to the current COVID-19 threat. 17 The purpose of the Field Epidemiology Training Program (FETP) is to train the population capacity to detect and respond to health threats and establish local experts in the area of epidemiology.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…18 Besides the protracted conflicts in many countries in the region, lack of infrastructure, limited resources, inadequate prevention control practices, poor preparedness capacity, and inadequate Awareness and response to Coronavirus disease (COVID-19) epidemic among the Arab Mhammad Saleh laboratory infrastructures and resources in many countries in the EMR are among the main barriers to adequately detect and respond to COVID-19. 17 Nsour et al in this study highlights the contribution of EMR's FETPs to the preparedness capacities in countries in the EMR to respond to the current COVID-19 threat. 17 The purpose of the Field Epidemiology Training Program (FETP) is to train the population capacity to detect and respond to health threats and establish local experts in the area of epidemiology.…”
Section: Discussionmentioning
confidence: 73%
“…15,16 For this reason, the present control method which depends on temperature screening is not a trustful method, and there is a critical need for accurate contact tracing starting from the day before the onset of symptoms as well as strict quarantine measures and monitoring before more chains of contagion are established. 17 A recent study showed that many countries in Africa including some countries that are part of the EMR have the variable capacity to respond to outbreaks and high vulnerability. 18 Besides the protracted conflicts in many countries in the region, lack of infrastructure, limited resources, inadequate prevention control practices, poor preparedness capacity, and inadequate Awareness and response to Coronavirus disease (COVID-19) epidemic among the Arab Mhammad Saleh laboratory infrastructures and resources in many countries in the EMR are among the main barriers to adequately detect and respond to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Their impact can be most apparent in situations of con ict and crises that disrupt public health systems and especially within the current shortage of resources. Several examples have clearly showed the success of FETP in responding to emergencies and disasters (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19). During the Middle East Respiratory Syndrome (MERS) outbreak in 2014 in Saudi Arabia, FETP graduates tackled numerous issues, including but not limited to, to redesigning the system to enable simultaneous real-time electronic reporting of suspected and con rmed cases to public health professionals who needed to take essential control and preventive actions on new cases (14).…”
Section: Discussionmentioning
confidence: 99%
“…During the Middle East Respiratory Syndrome (MERS) outbreak in 2014 in Saudi Arabia, FETP graduates tackled numerous issues, including but not limited to, to redesigning the system to enable simultaneous real-time electronic reporting of suspected and con rmed cases to public health professionals who needed to take essential control and preventive actions on new cases (14). FETP graduates are working nowadays in different ways to ght COVID-19 pandemic as they are actively participating in surveillance and screening at airports and other ports of entry, developing communication materials and guidelines and sharing information to health professionals and to the public (16). FETPs in the EMR showed success in building the epidemiologic capacity for public health workforce, improving countries' surveillance systems, and strengthening the health systems (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Hasan et al emphasizes the need to start training medical staff prior to the local start of the pandemic [14]. According to Al-Nsour et al training programs should cover rapid response teams, points of entries, contact tracing, lab and sample management, infection control, cases management, and other processes [27]. Standardized training is immensely helpful in time of crisis by improving the clinical abilities of practitioners, which is re ected in better preparation for dealing with emergencies [28].…”
Section: Discussionmentioning
confidence: 99%